ANALISIS FATWA MAJELIS ULAMA INDONESIA (MUI) DENGAN PENDEKATAN ISTISHAB - Agus Anwar Pahutar (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The main issue that is discussed in this paper is istishab. There are two research questions. First, does the Indonesian Ulema Council (MUI) use istishab in issuing its fatwas? If so, Second, on what issues does the Indonesian Ulema Council (MUI) use istishab? The research method is with Library Research. The results of this study show several findings, namely: The Indonesian Ulema Council uses istishab in issuing its fatwas. The use of istishab elements in the fatwa of the Indonesian Ulema Council is in matters of Family Law 1975-2010, there are 10 (ten) fatwas, namely on the issue of mixed marriages, three divorces at once, iddah death, adoption (appointment of children), marriage procedures, Mut'ah marriage, transgender status, inheritance from siblings/brothers with a single daughter, inheritance from different religions, and tourism marriage. Thus, according to the author, the Indonesian Ulema Council still tends to be conservative in issuing its fatwas. This can be seen from the dominance of the istishab method with an attitude that maintains the circumstances, habits and traditions that apply in the past for the present. So, this shows that the influence of the Shafiʻiy school is still very strong in Indonesia. This is evidenced by the fact that when issuing ijtihad in issuing fatwas, the Indonesian Ulema Council still uses istishab as a legal argument or method. Thus, the authors recommend that in issuing fatwas do not tend to be conservative. Because when it dominates, of course it has implications for the development and thinking of Islamic law in general. For example, the thought of Islamic law will find it difficult to move, as if circling in place, in the end Muslims will be considered old-fashioned and backward from other people, because they are considered unable to adapt to the times. Meanwhile, what is expected by the ummah is that MUI can become more innovative on issues that are increasingly complex and global, but without violating the teachings that have been emphasized by the Qur'an and Hadith of the Prophet SAW, in the sense that it must be within the limits set methodologically tolerated, in order to become a bridge for the advancement of the people and nation of Indonesia.